2016
DOI: 10.1007/s12035-015-9631-2
|View full text |Cite
|
Sign up to set email alerts
|

Acute Morphine, Chronic Morphine, and Morphine Withdrawal Differently Affect Pleiotrophin, Midkine, and Receptor Protein Tyrosine Phosphatase β/ζ Regulation in the Ventral Tegmental Area

Abstract: Pleiotrophin (PTN) and midkine (MK) are secreted growth factors and cytokines, proposed to be significant neuromodulators with multiple neuronal functions. PTN and MK are generally related with cell proliferation, growth, and differentiation by acting through different receptors. PTN or MK, signaling through receptor protein tyrosine phosphatase β/ζ (RPTPβ/ζ), lead to the activation of extracellular signal-regulated kinases (ERKs) and thymoma viral proto-oncogene (Akt), which induce morphological changes and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 65 publications
0
10
0
Order By: Relevance
“…The present work focused on the DH, a region in the brain known to be involved in memory. However, further studies should investigate whether IL-1β expression in other brain regions involved in opioid abuse, such as the ventral tegmental area and locus coeruleus, which regulate symptoms of opiate dependence and withdrawal (Garcia-Perez et al 2017;Kaufling and Aston-Jones 2015), may also contribute to HW-EFL and alter heroin withdrawal-induced weight changes.…”
Section: Discussionmentioning
confidence: 99%
“…The present work focused on the DH, a region in the brain known to be involved in memory. However, further studies should investigate whether IL-1β expression in other brain regions involved in opioid abuse, such as the ventral tegmental area and locus coeruleus, which regulate symptoms of opiate dependence and withdrawal (Garcia-Perez et al 2017;Kaufling and Aston-Jones 2015), may also contribute to HW-EFL and alter heroin withdrawal-induced weight changes.…”
Section: Discussionmentioning
confidence: 99%
“…Among genes in the cell adhesion molecules pathway impacted by morphine, PTPRC was under-expressed in morphine-treated pigs. Similarly, the tyrosine phosphatase receptor type Z ( PTPRZ1 ) was downregulated by chronic morphine treatment and upregulated after acute treatment in rodents [ 56 ]. Gene CDH1 participates in neurogenesis and cortical development and was under-expressed in the morphine-treated relative to the saline group ( Table 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Because opioid abusers undergo intermittent periods of withdrawal, impaired cognitive capabilities can be brought about withdrawal‐mediated impaired hippocampal function. It has been proposed that opioid withdrawal activates glial cells to release pro‐inflammatory cytokines (Garcia‐Perez et al., 2017; Hutchinson et al., 2009), including IL‐1β and TNFα, in several brain areas (Campbell et al., 2013). When pro‐inflammatory cytokines are released, they may cause brain damage (Colonna & Butovsky, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have shown that chronic use of opioid drugs have a negative impact on cognition (Welsch et al, 2020). Perez et al, 2017;Hutchinson et al, 2009), including IL-1β and TNFα, in several brain areas (Campbell et al, 2013). When pro-inflammatory cytokines are released, they may cause brain damage (Colonna & Butovsky, 2017).…”
Section: Discussionmentioning
confidence: 99%